The Pain of Implementing LINQ Providers. (Communications of the ACM, 2011)
The article discusses the use of LINQ (Language Integrated Query), a method of integrating data queries into computer programming language. It is noted that the premise of LINQ is very useful, but there are some difficulties associated with its implementation. These are addressed from the perspective of implementers and consumers. The article focuses on the example of building a LINQ provider for a NoSQL data store. It is recommended that each supported operation included be defined in a conventional way, and that a limited LINQ implementation is easier to manage.